Analisis Perbandingan Metode Harmonic Mean Filter dan Contraharmonic Mean Filter untuk mengurangi noise pada Citra Digital - Chairy, Amalia; Arifin, Nurhikmah; Insani, Chairi Nur (Journal of Computer and Information System ( J-CIS ), 2022)
The results of digital camera recordings to take digital images, there are often some disturbances that appear in the digital image called noise. The noise that is often found in digital images is Salt-Pepper Noise and Speckle Noise. An image that has noise usually occurs due to an error in image retrieval techniques. Noise that usually appears is spots on the image, it is necessary to reduce noise by using the right filter method so that the resulting image matches the original. One of the filter methods to reduce noise is the harmonic mean-filter and contra-harmonic mean filter methods. From the calculation results of the average Mean Square Error (MSE) and Peak Signal to Noise Ratio (PSNR), it can be concluded that the Harmonic Mean Filter method is better at reducing salt & pepper noise. While the Contra-Harmonic Mean Filter method is better at reducing speckle noise.